THE STUDY OF THE LEARNING ACHIEVEMENT OF SARASAS EKTRA SCHOOL SYMPHONIC BAND MEMBERS IN PRACTICING CLARINET SKILLS EXERCISES ABOUT THE DEFTNESS OF FINGERING BASED ON THE THEORIES OF CARL BAERMANN - Ditthakamonphat, Thankamon; Yanderm, Sitsake (Fine Arts Journal: Srinakharinwirot University, 2021)
The current study aims to examine the learning achievement and the satisfaction level of students in the Sarasas Ektra School symphonic band in practicing clarinet performing skills exercises about the deftness of the fingering based on the theories of Carl Baermann. The sample consisted of ten students playing the clarinet in Sarasas Ektra School symphonic band in the second semester of the 2019 academic year. The research instruments consisted of (1) clarinet performing skills exercises in the deftness of the fingering, (2) the achievement test of clarinet performing skills, and (3) the survey of the satisfaction level on clarinet performing skills exercises. The statistics used for the data analysis included mean, percentage and standard deviation. The results were as follows: (1) after learning with clarinet performing skills exercise in the deftness of the fingering based on the theories of Carl Baermann, students received higher scores with a statistical significance of .05 and (2) students showed their satisfaction at the highest level (=4.74).